Virtual Reality for Mitigating Fall Risk in the Elderly: A Bibliometric Analysis - Dharmansyah, Dhika; Adikusuma Suparto, Tirta; Pragholapati, Andria (STIKep PPNI Jawa Barat, 2025)
Background: Fall risk among the elderly is a global health concern impacting quality of life and mortality. Virtual Reality (VR) is gaining traction as a tool in fall prevention strategies. Objective: To map research trends, authorship, country productivity, and keyword themes related to VR in fall risk mitigation using bibliometric methods. Methods: A bibliometric study of 166 publications (2007–2025) retrieved from Scopus was conducted using VOSviewer and Scopus analytics. Indicators included author productivity, subject areas, and keyword clusters. Results: The number of publications has risen markedly since 2018, with the highest output in 2023. The United States, UK, and Israel led in research output. Research themes focused on VR-based balance training, rehabilitation, and psychological interventions such as fear of falling. Conclusion: VR is a growing multidisciplinary field in elderly care. These insights inform future research directions and intervention policy.